LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI SECARA DARING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMA KELAS XI PADA SAAT PADEMI COVID-19 - Ilmi Aliyah; Heris Hendriana; Siti Fatimah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
Currently it is known to use online or through distance learning (PPJ) teachers when explaining lessons using applications (Zoom, Google chrome, Whatshap, Google from) of course learning through online media or learning (online) also affects other teachers, especially teachers guidance and counseling, as teachers are required to be active on student psychology, guidance and counseling teachers play a role in facilitating the development of students' potential in the personal, social, learning, career, and personal development aspects of students, so that this becomes a new challenge for guidance and counseling teachers in providing services during the Covid-19 pandemic. The purpose of this study is to describe the factors that trigger low learning motivation of students in class XI IPS 3 at SMA Darul Falah Cihampelas during the covid-19 outbreak. This study used descriptive qualitative method. Data collection techniques are using observation, interviews and documentation. Based on the results of the study, the factors that caused low learning motivation for the six students were students. It often happened that students who did not excel were not caused by their lack of ability, but because there was no motivation to learn so they did not try to direct all their abilitie the traditional.  Keywords: Learning Motivation, Group Guidance, Pademic Covid-19